Operation Effect Analysis of Dynamic Stabilizer Considering the Characteristics of Fasteners - CHEN Taimao; WANG Lihua; HUANG Hongyi; WANG Jiongli; ZHAO Zemin; JIANG Wei (Chengshi guidao jiaotong yanjiu)
［Objective］ Research is conducted on the influence and significance of the excitation frequency of the dynamic stabilization device and the mechanical characteristics of rail fasteners on the operation effect of the dynamic track stabilizer in order to provide some reference for the operation of the dynamic stabilizer. ［Method］ Based on the multi-body system dynamics theory, a dynamic stabilization device-track dynamics model considering the mechanical characteristics of rail fasteners is established. A rigid-flexible coupling dynamics simulation model of the dynamic stabilization device-ballast bed is established by using the finite element method. With the excitation frequency of the dynamic stabilization device, the lateral stiffness and the lateral damping of the fastener as research factors, and the lateral acceleration response of the sleeper as the evaluation index of stable operation effect, a numerical simulation analysis is carried out to obtain the significance of the influencing factors for the dynamic stabilization operation effect. ［Result & Conclusion］ With the increase of the excitation force amplitude of the dynamic stabilization device, both the lateral displacement and the acceleration of the sleeper increase monotonically. When the excitation frequency gradually increases, the lateral displacement of the sleeper decreases monotonically, while the lateral acceleration first decreases and then increases. The obtained optimal excitation frequency range of the dynamic stabilization device is from 30 to 36 Hz. Increasing the lateral stiffness of the rail fastener leads to an increase of the sleeper lateral acceleration. Increasing the lateral damping of the rail fastener will reduce the sleeper lateral acceleration. Based on the response surface method, three factors influencing the sleeper lateral acceleration are excitation frequency, fastener lateral stiffness and fastener lateral damping in order of significance.